Harnessing the therapeutic potential of bacterial extracellular vesicles via functional peptides - Yejiao Shi; Zelin Zheng; Wen Wang; Honggang Hu (Interdisciplinary Medicine)
Abstract Bacterial extracellular vesicles (BEVs) are nanoscale vesicles secreted by bacteria. They possess lipid bilayer membranes and contain multiple periplasmic and cytoplasmic components, facilitating their intercellular communications through transferring of various bioactive molecules. Considering their intrinsic structure, delivery capacity, immunogenic property, facile production, and versatile modification, more and more studies have exploited BEVs directly as therapeutic agents or engineered as delivery vehicles for the disease treatment. Nevertheless, the unprecedented upsurge of studies in BEVs highlighted the burgeoning need for tailoring them with enhanced therapeutic efficacies including specific targeting, subcellular penetration, pathological site retention, and so on. With this aspect, functional peptides with either targeting, penetrating, immunostimulating, specific biofunctions, or self‐assembly exhibit their power to open new avenues. Functional peptides can be either modified on the surface, encapsulated inside the bilayer membranes, or even self‐assembled into hydrogel embedding around BEVs to fully unleash the therapeutic potential of BEVs. Herein, the present perspective is dedicated to overview the most recent advancements in exploring functional peptides for bridging BEVs to disease treatment, and to provide valuable insights for the future development of innovative therapeutic modalities.